Political and Legal Position in the Mahmud Village Society (International Journal of Education and Literature, 2025)
Mahmud Village, located in Bandung Regency, is one of the indigenous communities that continues to uphold its customary laws and traditions amidst the tide of modernization. This research aims to explore and analyze the political position and role of customary law within this community, with a focus on how customary norms and rules are implemented, maintained, and passed down amidst the dynamics of social change and interactions with state law. Using a qualitative ethnographic approach, data was collected through participant observation, in-depth interviews with customary leaders, community members, and government officials, and a review of relevant literature. The research results indicate that customary law holds a highly significant and respected position among the residents of Mahmud Village. The customary figure, known as the "Kuncen," holds the highest authority in enforcing customary law, leading traditional ceremonies, and resolving various disputes, ranging from marriage and inheritance matters, ceremonial procedures, to mediation mechanisms between residents. Although customary law has strong social power, its application is not entirely independent of the influence of state law, particularly in cases that intersect with criminal law or national legislation. These findings reveal a process of adaptation, where the Mahmud Village indigenous community strives to maintain traditional values while adapting customary rules to remain relevant to current demands. This research confirms that customary law functions not only as a social regulatory system but also as a bulwark of cultural identity and a vital instrument for the sustainability of indigenous communities. Therefore, understanding and recognizing customary law is crucial for maintaining harmony between local traditions and the national legal framework.